Tornwaldt's Cyst - Comments on Clinical Cases - Vlad Budu; Tatiana Decuseară; Andreea-Nicoleta Costache; Lavinia Sava; B Dima; M Tuşaliu (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Tornwaldt's cyst represents a benign tumor which develops in the midline of the nasopharyngeal mucosa. Due to the fact that it doesn't usually cause any symptoms, it is often discovered incidentally during a nasal endoscopy or another imaging investigation (either CT or MRI). Treatment is only advised when the cyst becomes symptomatic. In this paper, the authors aim to illustrate the optimal approach when dealing with a Tornwaldt's cyst and to underline the importance of a correctly executed endoscopic surgery.